De-escalation of Broad Spectrum Antibiotics Following Negative Cultures in Pneumonia: Rates and Outcomes. (4th October 2017) - Deshpande, Abhishek; Richter, Sandra S; Haessler, Sarah; Brizendine, Kyle; Lindenauer, Peter; Yu, Pei-Chun; Zilberberg, Marya D; Imrey, Peter; Higgins, Thomas; Rothberg, Michael
Abstract: Background: For patients at risk for multidrug resistant organisms, IDSA/ATS guidelines recommend empiric therapy with 1 agent against methicillin-resistant Staphylococcus aureus (MRSA) and another against Pseudomonas . Following negative cultures, guidelines are unclear regarding antibiotic de-escalation. We assessed de-escalation and associated outcomes in a cohort of pneumonia patients with negative cultures. Methods: We included adults admitted with pneumonia from 2010- 2015 to 168 US hospitals if they had blood/respiratory cultures and received vancomycin together with an antipseudomonal drug other than a quinolone by hospital day 1. We excluded patients with positive cultures, death or discharge by day 4. De-escalation was defined as stopping both drugs by day 4, but continuing another antibiotic. Patients were matched on propensity for de-escalation and compared on late deterioration, inpatient mortality, length of stay (LOS), cost and 30-day readmission. The propensity model included demographics, co-morbidities and treatments on day 4, which served as proxies for clinical severity. We also compared adjusted outcomes across hospital quartile of de-escalation. Results: Of 22, 400 patients included, 4121 (18.4 %) had both drugs stopped within 4 days. Median age was 72 years, 56% were female, and 39% were admitted to the intensive care unit (ICU). Compared with patients without de-escalation, those de-escalated had similar demographics, but fewer co-morbidities and less severe disease at days 1 and 4. After propensity-matching, there were no significant differences in 83 variables. In the matched sample, de-escalated patients had lower odds of inpatient mortality (OR 0.71, 95% CI 0.60 – 0.83), subsequent transfer to ICU (OR 0.31; 95% CI 0.19 – 0.52), LOS (OR 0.79, 95% CI 0.77 – 0.80) and lower costs (OR 0.79, 95% CI 0.77 – 0.80). Hospital rates of de-escalation ranged from 0–67%. Hospital de-escalation quartile was not significantly associated with any outcome. Conclusion: In a sample of US hospitals, <20% of pneumonia patients had antibiotic coverage de-escalated following negative cultures, but it varied widely by hospital. Hospitals with high rates of de-escalation did not have worse outcomes. Following negative cultures, de-escalation appears safe in selected patients. Disclosures: S. S. Richter, bioMerieux: Investigator, Research support; BD Diagnostics: Investigator, Research support; Roche: Investigator, Research support; BioFire: Investigator, Research support; OpGen: Investigator, Research support; S. Haessler, AHRQ: Investigator, Research grant; P. C. Yu, AHRQ: Investigator, Research grant; M. D. Zilberberg, Astellas: Consultant and Investigator, Research support; Merck: Consultant and Investigator, Research support; The Medicines Company: Consultant and Investigator, Research support; Shionogi: Consultant and Investigator, Research support; Pfizer: Consultant and Investigator, Research support; Theravance: Consultant and Investigator, Research support; J&J: Shareholder, Shareholder; M. Rothberg, AHRQ: Investigator, Research grant